Safety, tolerability and pharmacokinetics/pharmacodynamics of the adrenomedullin antibody adrecizumab in a first‐in‐human study and during experimental human endotoxaemia in healthy subjects. (3rd July 2018) - Geven, Christopher; van Lier, Dirk; Blet, Alice; Peelen, Roel; ten Elzen, Bas; Mebazaa, Alexandre; Kox, Matthijs; Pickkers, Peter
Abstract : Aims: Adrenomedullin (ADM) is an important regulator of endothelial barrier function and vascular tone, and may represent a novel treatment target in sepsis. The non‐neutralizing ADM antibody adrecizumab has shown promising results in preclinical sepsis models. In the present study, we investigated the safety, tolerability and pharmacokinetics (PK)/pharmacodynamics of adrecizumab in a first‐in‐man study and in a second study during experimental human endotoxaemia. Methods: Forty‐eight healthy male volunteers were enrolled in two randomized, double‐blind, placebo‐controlled phase I studies. In both studies, subjects received placebo or one of three doses of adrecizumab ( n = 6 per group). In the second study, a bolus of 1 ng kg –1 endotoxin was followed by infusion of 1 ng kg –1 h –1 endotoxin for 3 h to induce systemic inflammation, and the study medication infusion started 1 h after endotoxin bolus administration. Results: Adrecizumab showed an excellent safety profile in both studies. PK analyses showed proportional increases in the maximum plasma concentration of adrecizumab with increasing doses, a small volume of distribution, a low clearance rate and a terminal half‐life of 14 days. adrecizumab elicited a pronounced increase in plasma ADM levels, whereas levels of mid‐regional pro‐adrenomedullin remained unchanged, indicating that de novo synthesis of ADM was not influenced. In the second study, no effects of adrecizumab on cytokine clearance were observed, whereas endotoxin‐induced flu‐like symptoms resolved more rapidly. Conclusions: Administration of adrecizumab is safe and well tolerated in humans, both in the absence and presence of systemic inflammation. These findings pave the way for further investigation of adrecizumab in sepsis patients.